Angiotensin II type 1 receptor antagonist attenuates lacrimal gland, lung, and liver fibrosis in a murine model of chronic graft-versus-host disease. - Saori Yaguchi; Yoko Ogawa; Shigeto Shimmura; Tetsuya Kawakita; Shin Hatou; Shingo Satofuka; Shigeru Nakamura; Toshihiro Imada; Hideyuki Miyashita; Satoru Yoshida; Tomonori Yaguchi; Yoko Ozawa; et al. (PLoS ONE, 2013)
Chronic graft-versus-host disease (cGVHD), a serious complication following allogeneic HSCT (hematopoietic stem cell transplantation), is characterized by systemic fibrosis. The tissue renin-angiotensin system (RAS) is involved in the fibrotic pathogenesis, and an angiotensin II type 1 receptor (AT1R) antagonist can attenuate fibrosis. Tissue RAS is present in the lacrimal gland, lung, and liver, and is known to be involved in the fibrotic pathogenesis of the lung and liver. This study aimed to determine whether RAS is involved in fibrotic pathogenesis in the lacrimal gland and to assess the effect of an AT1R antagonist on preventing lacrimal gland, lung, and liver fibrosis in cGVHD model mice. We used the B10.D2→BALB/c (H-2(d)) MHC-compatible, multiple minor histocompatibility antigen-mismatched model, which reflects clinical and pathological symptoms of human cGVHD. First, we examined the localization and expression of RAS components in the lacrimal glands using immunohistochemistry and quantitative real-time polymerase chain reaction (PCR). Next, we administered an AT1R antagonist (valsartan; 10 mg/kg) or angiotensin II type 2 receptor (AT2R) antagonist (PD123319; 10 mg/kg) intraperitoneally into cGVHD model mice and assessed the fibrotic change in the lacrimal gland, lung, and liver. We demonstrated that fibroblasts expressed angiotensin II, AT1R, and AT2R, and that the mRNA expression of angiotensinogen was greater in the lacrimal glands of cGVHD model mice than in controls generated by syngeneic-HSCT. The inhibition experiment revealed that fibrosis of the lacrimal gland, lung, and liver was suppressed in mice treated with the AT1R antagonist, but not the AT2R antagonist. We conclude that RAS is involved in fibrotic pathogenesis in the lacrimal gland and that AT1R antagonist has a therapeutic effect on lacrimal gland, lung, and liver fibrosis in cGVHD model mice. Our findings point to AT1R antagonist as a possible target for therapeutic intervention in cGVHD.